2018
DOI: 10.1049/iet-pel.2017.0090
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic buck–boost converter with positive output voltage and minimum ripple point design

Abstract: This study presents a novel topology of a buck-boost converter that features: (i) quadratic voltage gain; (ii) positive output voltage with respect to the input; (iii) continuous input current. Moreover, as the main contribution, (iv) it features a minimum ripple design, for which input current and output voltage ripples are simultaneously cancelled at the desired operating point. It is also shown that even though the duty cycle deviates from a nominal minimum ripple point, the converter exhibits a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 19 publications
(49 reference statements)
0
106
0
Order By: Relevance
“…There are other effective methods to increase output voltage which have particular pros and cons [10][11][12][13][14][15][16]. Combination of switched-capacitor and switched-inductor techniques with the conventional converters are two of the methods that can be mentioned [13,16]. Also, interleaved configurations of DC-DC converters are used due to their advantages such as reduction of input current ripple.…”
Section: Introductionmentioning
confidence: 99%
“…There are other effective methods to increase output voltage which have particular pros and cons [10][11][12][13][14][15][16]. Combination of switched-capacitor and switched-inductor techniques with the conventional converters are two of the methods that can be mentioned [13,16]. Also, interleaved configurations of DC-DC converters are used due to their advantages such as reduction of input current ripple.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, additional components like inductors, capacitors and diodes should be used as proposed in [5]. The other kind of extended converter based on boost is quadratic boost converter which consists of a reformed cascaded boost converter [10][11][12]. Its voltage gain is low and can be improved by adding a coupled inductor.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in Kaouane et al (2015) and Premkumar and Sumithira (2019b) reported converters with two MOSFET switches and hybrid boost, respectively, for solar photovoltaic (PV) systems to improve the output voltage gain along with the proper tracking technique. The quadratic buckboost converter was reported by Rosas-Caro et al (2018b) with the conversion output voltage and continuous input current with positive polarity.…”
Section: Introductionmentioning
confidence: 99%